2007
DOI: 10.1111/j.1399-6576.2007.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine abolishes the myocardial protective effect of sevoflurane post‐conditioning

Abstract: Sevourane-induced post-conditioning effectively protected myocardium against reperfusion damage and its cytoprotection was reversed by 20 microg/ml lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Sevoflurane, a volatile anesthetic, was demonstrated to have cardioprotective effect in ischemic and reperfused rat hearts by postconditioning (Obal et al, 2005;. Obal et al(2005) has elucidated that the adenosine triphosphate-sensitive potassium (K ATP ) channel did involve the postconditioning of sevoflurane, which was in line with our previous results (Yan et al, 2008). Nevertheless, it might not be the only mediator underlying the complicating pathological lesion (Zhao and Vinten-Johansen, 2006).…”
Section: Introductionsupporting
confidence: 78%
“…Sevoflurane, a volatile anesthetic, was demonstrated to have cardioprotective effect in ischemic and reperfused rat hearts by postconditioning (Obal et al, 2005;. Obal et al(2005) has elucidated that the adenosine triphosphate-sensitive potassium (K ATP ) channel did involve the postconditioning of sevoflurane, which was in line with our previous results (Yan et al, 2008). Nevertheless, it might not be the only mediator underlying the complicating pathological lesion (Zhao and Vinten-Johansen, 2006).…”
Section: Introductionsupporting
confidence: 78%
“…Moreover, administration of isoflurane immediately before and during early reperfusion after prolonged ischemia protected the myocardium against infarction (Shim et al, 2007). Recently, experimental sevoflurane postconditioning improved postischemic recovery and reduced myocardial infarct size (Yan et al, 2008). Sevoflurane postconditioning possesses a strong antiarrhythmic effect against reperfusion-induced ventricular fibrillation by conversion of ventricular fibrillation into regular rhythm (Zhang et al, 2009).…”
Section: Anesthetic Postconditioningmentioning
confidence: 99%
“…The group of Schlack firstly reported that lidocaine, a potent inhibitor not only of sodium channels but also of ATP-sensitive potassium channels, blocked (at supratherapeutic concentrations) cardioprotection induced by ischaemic preconditioning in isolated rat hearts [53]. This effect has been recently recapitulated for sevoflurane postconditioning under the same experimental conditions [54]. Similarly, the former group reported that ketamine completely abolished the IPreC-related cardioprotection both in vitro [55] and in vivo [56], an effect that was stereospecific for the R (À) enantiomer.…”
Section: Cardioprotection Attenuation/blockadementioning
confidence: 87%